PENERAPAN MODEL KOOPERATIF TIPE TEAM GAMES TOURNAMENT PADA PEMBELAJARAN TRIGONOMETRI DI SMA - Pangestu, Ricki Aji; Halini, Halini; Ahmad BS, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to know and describe the effeectiveness implementation of cooperative type Team Games Tournament in Trigonometry learning at SMA N 08 Pontianak. The research method used in this study was pre-experimental with a one shot case study design. The aspects used to determine the effectiveness of the team games tournament model were the activities of students, the application of teachers in managing learning, and student learning outcomes. The data collection tool used was a test of student learning outcomes, which contains 5 essay questions, observation sheets the process of implementing teachers in the management of learning, observation sheets of student activities, research data analyzed descriptively. It was obtained that the activities of the students were classified as quite active at 70%. the teacher's implementation process in managing learning is very good, namely 3,635. Classical student mastery learning Â was not fulfilled, there were 27 students or 77% of student who achieve the minimum completeness scores. Learning by using the team games tournament model on trigonometry learning in Pontianak 8 High School is said to be ineffective.Â Keywords: Application,Â Cooperative Team Games Tournament Model, Trigonometry Learning